Suvṛttatilaka of Kṣemendra : text with Sanskrit commentary and English translation - Kṣemendra (New Bharatiya Book Corp., 2007)
Classical work on Sanskrit poetics; includes Bhạ̄ratīvr̥tti and English translation.